Inhibition of the classical pathway of the complement cascade prevents early dendritic and synaptic degeneration in glaucoma. Issue 1 (December 2016) - Williams, Pete; Tribble, James; Pepper, Keating; Cross, Stephen; Morgan, B; Morgan, James; John, Simon; Howell, Gareth
Abstract Background Glaucoma is a complex, multifactorial disease characterised by the loss of retinal ganglion cells and their axons leading to a decrease in visual function. The earliest events that damage retinal ganglion cells in glaucoma are currently unknown. Retinal ganglion cell death appears to be compartmentalised, with soma, dendrite and axon changes potentially occurring through different mechanisms. There is mounting evidence from other neurodegenerative diseases suggesting that neuronal dendrites undergo a prolonged period of atrophy, including the pruning of synapses, prior to cell loss. In addition, recent evidence has shown the role of the complement cascade in synaptic pruning in glaucoma and other diseases. Results Using a genetic (DBA/2J mouse) and an inducible (rat microbead) model of glaucoma we first demonstrate that there is loss of retinal ganglion cell synapses and dendrites at time points that precede axon or soma loss. We next determine the role of complement component 1 (C1) in early synaptic loss and dendritic atrophy during glaucoma. Using a genetic knockout ofC1qa (D2.C1qa -/- mouse) or pharmacological inhibition of C1 (in the rat bead model) we show that inhibition of C1 is sufficient to preserve dendritic and synaptic architecture. Conclusions This study further supports assessing the potential for complement-modulating therapeutics for the prevention of retinal ganglion cell degeneration in glaucoma.